Visian® ICLV4c™ and Artiflex®: Comparative Analysis with the HD Analyser™ and Integration with Subjective Performance and Anatomical Parameters - Baptista, Pedro Manuel (2021)
Purpose: To analyze and compare the mid-term objective and subjective performance of two phakic intraocular lenses (PIOLs) - Visian® ICL™ V4c and Artiflex® and to correlate those results with anatomical parameters. Patients and methods: Observational retrospective study including thirty patients (15 for each PIOL) randomly selected from those who underwent bilateral implantation of one of the PIOLs (60 eyes were analysed). Uncorrected and corrected distance visual acuities (UDVA and CDVA), anterior chamber structural parameters, and corneal endothelial cells density and morphology were evaluated. Quality of vision was assessed both subjectively with a questionnaire, and objectively using a double-pass technology optical quality analysis system. Results: At the end of follow-up the Artiflex® group showed better UDVA (0.95±0.11 vs 0.99±0.05, p=0.027) and higher proportion of eyes reaching at least 20/20 (28/30 vs 18/30, p=0.005). Excellent and similar objective scatter index (1.79±0.9 vs 2.14±1.6, p=0.306) and modular transfer function cutoff frequency (26.91±9.2 vs 26.51±11.9, p=0.784) results were achieved in the HD Analyzer® and the questionnaire showed comparable high Satisfaction (55.7±3.5 vs 54.3±5.4, p=0.386) and low Dysphotopsia Scores (3.1±1.8 vs 2.1±2.2, p=0.213). The ICL group showed inferior anterior chamber volume (p<0.001), and angle (p<0.001) and superior pupillary diameter (p=0.007). Minimum follow-up was 24 months. Conclusion: Both the Visian® ICLV4c™ and the Artiflex® showed excellent optical performance through the HD AnalyzerTM technology, translated in high patient satisfaction. Overall, both PIOLs showed similar safety, predictability, stability and effectiveness of for the reduction of high sphero-cylindrical refractive errors, despite better UDVA results with the Artiflex®.